Pengaruh Kepemimpinan, Lingkungan Kerja Fisik, dan Kompensasi pada Kinerja Karyawan UD. Terus di Bali - Yogi Antara, I Ketut Kusuma (E-Jurnal Manajemen; Vol 4 No 6 (2015), 2015)
UD. Terus was established in 1993, faces a decline in employee performance that need to be solved. This study aim is to determine the effect of leadership, physical work environment, and compensation on employee performance. This research was conducted on employees of UD. Terus in Bali. The sample was 91 employees by using saturation method. Data was collected through 5-point Likert scale questionnaires to measure 30 indicators. The analysis technique used is multiple linear regression analysis. The results show that leadership, physical work environment, and compensation is positively effect employee performance. Additionally, 80.8 percent of variation of performance is determined by leadership (X1), physical work environment (X2), and compensation (X3), while the remaining (19.2 percent) is contributed by other variables that are not included in this research model.
Keywords: , leadership , physical work environment, compensation